2022
DOI: 10.1145/3517341
|View full text |Cite
|
Sign up to set email alerts
|

Authenticity, Integrity, and Replay Protection in Quantum Data Communications and Networking

Abstract: Quantum data communications and networking involve classical hardware and software. Quantum storage is sensitive to environmental disturbances that may have malicious origins. Teleportation and entanglement swapping, two building blocks for the future quantum Internet, rely on secure classical bit communications. When lack of authenticity, integrity and replay protection may have a high impact, quantum data communications are at risk and need to be protected. Building upon quantum cryptography and random gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Fundamental properties are authenticity, confidentiality, integrity, and replay protection. [7][8][9] We focus on the authenticity, confidentiality, integrity, and replay protection of quantum messages. An authenticity attack deceives the destination about the trustworthy source of a message.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fundamental properties are authenticity, confidentiality, integrity, and replay protection. [7][8][9] We focus on the authenticity, confidentiality, integrity, and replay protection of quantum messages. An authenticity attack deceives the destination about the trustworthy source of a message.…”
Section: Introductionmentioning
confidence: 99%
“…An authenticity attack deceives the destination about the trustworthy source of a message. 7,9 Mitigating the authenticity attack requires a proof of the source identity in a message. Confidentiality protection mitigates the risk of disclosing or leaking information contained in messages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, challenges exist in relation to secret key rate, transmission distance, size, cost, imperfect physical devices, signal-to-noise ratio, and practical security [3,18,19]. Moreover, other challenges are associated with imperfections in communication channels, for instance, quantum data communications and networking, underwater communication, satellite communication, and fiber-optic communication [20][21][22][23][24]. A QCC protocol is ideally secure only when it employs perfect single-photon sources and detectors.…”
Section: Introductionmentioning
confidence: 99%
“…The work in [21] showed that the Clifford code QMA scheme can also be extended to include replay detection.…”
Section: Definitionmentioning
confidence: 99%